Optimizing Thin Layer Chromatography (TLC) Eluent Composition for Compound Content Separation the Ethanolic Extract of Sponge and Ascidia - Lintang, Rosita; Losung, Fitje; Menajang, Febry I. S.; Sumilat, Deiske Adeliene (Jurnal Ilmiah Platax, 2024)
An optimization study of the KLT eluent composition was carried out on the ethanolic extracts of 3 ascidian samples (Ascd-2, Ascd-3, Ascd-4) and 2 sponge samples (Spons-2 and Spons-3). The Ascidia and Sponge marine invertebrate samples were collected from Malalayang, Manado City's coastal waters, and were not identified. This research is a preliminary test to determine the best eluent composition to separate the compounds in the ascidian and sponge sample extracts. Extracted samples with ethanol solvent using the maceration method for 3 x 24 hours at room temperature followed by evaporation at 400C to obtain a thick ethanol extract. The composition of the eluent used is as follows: Hexane: Ethyl Acetate = 3: 7, Hexane: Ethyl Acetate = 2: 3, Hexane: Ethyl Acetate = 1: 9, Methanol: Ethyl Acetate = 1:1, and 100% Methanol. KLT analysis of the extracts from the ascidia and sponge samples showed that most of the variations in eluent composition used could not separate the compound components in the extracts, except the 100% methanol composition which could separate the compounds in the spongs 3 samples. Keywords : Eluent ; Marine Invertebrate; Optimation ; TLC Abstrak Telah dilakukan studi optimasi komposisi eluen KLT terhadap ekstrak etanol dari 3 sampel Ascidia (Ascd-2,Ascd-3,Ascd-4) dan 2 sampel Spons (Spons-2 dan Spons-3). Sampel avertebrata laut Ascidia dan Spons berasal dari perairan pantai Malalayang, Kota Manado dan belum diidentifikasi jenisnya. Penelitian ini merupakan suatu uji pendahuluan yang bertujuan menentukan komposisi eluen terbaik untuk memisahkan senyawa yang terkandung dalam ekstrak sampel ascidian dan spons. Ekstraksi sampel dengan pelarut etanol menggunakan metode maserasi selama 3 x 24 jam pada suhu ruang dan kemudian dievaporasi pada suhu 400C untuk mendapatkan ekstrak etanol kental. Adapun komposisi eluen yang digunakan adalah sebagai berikut: Heksana : Etil Asetat= 3 : 7, Heksana : Etil Asetat = 2 : 3, Heksana : Etil Asetat = 1 : 9, Metanol : Etil Asetat = 1 : 1, dan Metanol 100%. Analisis KLT terhadap ekstrak sampel ascidia dan spons memperlihatkan bahwa sebagian besar variasi komposisi eluen yang digunakan tenyata tidak dapat memisahkan komponen senyawa dalam ekstrak, kecuali komposisi 100% methanol yang dapat memisahkan senyawa pada sampel Spons-3. Kata Kunci : Avertebrata Laut; Eluen; KLT: Optimasi